2016
DOI: 10.1161/strokeaha.116.014166
|View full text |Cite
|
Sign up to set email alerts
|

Strictly Lobar Cerebral Microbleeds Are Associated With Cognitive Impairment

Abstract: 2 In addition to being an age-related cerebrovascular abnormality, [3][4][5] CMBs are associated with dementia. The prevalence of CMBs is reported to be higher in patients with Alzheimer's disease (AD) and vascular dementia compared with the general population. 6 The mechanisms underlying CMBs and their effects on neuropsychological functions are subjects of active research.CMB in different locations might be related to different clinical manifestations. 3,7,8 The incidence of both CMB types increases with age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 43 publications
4
33
2
Order By: Relevance
“…Although their clinical significance continues to be assessed, data from population‐based cohort studies show that CMBs are associated with increased risk of both future ischaemic stroke (IS) and intracerebral haemorrhage (ICH), recurrent IS and ICH, and both cardiovascular‐related and all‐cause mortality . Emerging data suggest CMBs are associated with reduced global cognitive function and both vascular and all‐cause dementia …”
Section: Introductionmentioning
confidence: 99%
“…Although their clinical significance continues to be assessed, data from population‐based cohort studies show that CMBs are associated with increased risk of both future ischaemic stroke (IS) and intracerebral haemorrhage (ICH), recurrent IS and ICH, and both cardiovascular‐related and all‐cause mortality . Emerging data suggest CMBs are associated with reduced global cognitive function and both vascular and all‐cause dementia …”
Section: Introductionmentioning
confidence: 99%
“…(Chung et al, 2016) It is also conceivable that disruption of cortico-nigrostriatal and thalamo-cortical pathways by strategically placed deep/mixed CMBs could contribute to cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have described regional distribution of lobar CMBs. A community-based study using SWI on 3T-MRI showed that the occipital lobe had the most numerous CMBs followed by the T A B L E 2 Three-group comparison: SL-CMBs·M-CMBs·D-CMBs frontal lobe (Chung et al, 2016). In patients with AD, CMBs have been found to be most numerous in the occipital lobe, followed by the temporal lobe, in studies using T2* on 1.5T-MRI (Pettersen et al, 2008) or SWI on 3T-MRI (Uetani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%